Cognitive behavioural therapy for insomnia reduces sleep apnoea severity: a randomised controlled trial. Issue 2 (17th May 2020) - Sweetman, Alexander; Lack, Leon; McEvoy, R. Doug; Antic, Nick A.; Smith, Simon; Chai-Coetzer, Ching Li; Douglas, James; O'Grady, Amanda; Dunn, Nicola; Robinson, Jan; Paul, Denzil; Eckert, Danny; et al.
Insomnia and obstructive sleep apnoea (OSA) frequently co-occur and may be causally related through sleep fragmentation and/or hyperarousal mechanisms. Previous studies suggest that OSA treatment can improve insomnia severity. However, the effect of insomnia treatment on OSA severity has not been investigated. We performed a randomised controlled trial to investigate the effect of cognitive behavioural therapy for insomnia (CBTi) on OSA severity, controlling for potential sleep-stage and posture effects. 145 patients with comorbid insomnia (International Classification of Sleep Disorders, 3rd Edn) and untreated OSA (apnoea–hypopnoea index (AHI) ≥15 events·h −1 sleep) were randomised to a four-session CBTi programme or to a no-treatment control. Overnight sleep studies were completed pre- and post-treatment to measure AHI, arousal index and sleep architecture, to investigate the effect of intervention group, time, sleep stage (N1–3 or REM) and posture (supine or nonsupine) on OSA severity. The CBTi group showed a 7.5 event·h −1 greater AHI difference (mean (95% CI) decrease 5.5 (1.3–9.7) events·h −1, Cohen's d =0.2, from 36.4 events·h −1 pre-treatment) across sleep-stages and postures, compared to control (mean increase 2.0 (−2.0–6.1) events·h −1, d =0.01, from 37.5 events·h −1 at pre-treatment; interaction p=0.012). Compared to control, the CBTi group also had a greater reduction in total number (mean difference 5.6 (0.6–10.6) greater overall reduction; p=0.029) and duration of nocturnal awakenings (mean difference 21.1 (2.0–40.3) min greater reduction; p=0.031) but showed no difference in the arousal index, or sleep architecture. CBTi consolidates sleep periods and promotes a 15% decrease in OSA severity in patients with comorbid insomnia and OSA. This suggests that insomnia disorder may exacerbate OSA and provides further support for treating insomnia in the presence of comorbid OSA. Cognitive behavioural therapy for insomnia consolidates sleep periods and promotes a 15% decrease in obstructive sleep apnoea severity in patients with comorbid insomnia and sleep apnoea https://bit.ly/3e4iPgB